Retirement Home? Ageing Migrant Workers in France and the Question of Return - Hunter, Alistair (Cham Springer Nature, 2018)
Aging migrants; Return and circulation migration; Migrant worker hostels in France; Social systems; Older North and West African men
English
Keywords: Development studies; Aging migrants; Return and circulation migration; Migrant worker hostels in France; Social systems; Older North and West African men